Analysis of electrocorticographic signal activity characteristics in motor cortex glioma. - ZHAO Wenyu; LIU Yan-hui; MAO Qing; JIANG Ning; HE Jia-yuan; YANG Yuan (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To investigate the electrocorticographic signal activity characteristics in glioma located in the motor area. Methods Total 8 patients undergoing awake craniotomy for motor area- involved glioma in West China Hospital, Sichuan University between October 2024 and February 2025 were enrolled. During the awake state, 2 min resting-state electrocorticographic signals were continuously recorded. After preprocessing steps including filtering, signal activity characteristics across θ, α, β, γ1, γ2, γ3, γ4 frequency bands were extracted. Using preoperative MRI data and subdural electrode parameters, individualized brain and electrode models were reconstructed. The spatial relationships between electrodes and tumors during data acquisition were coregistered onto the brain models. Based on the tumor invasion degree into brain tissue beneath the electrodes, the 762 validated electrodes were categorized into 3 groups: normal brain tissue group (n = 460), tumor-invaded cortex group (n = 274) and tumor-non-invaded cortex group (n = 28). Results In the frequency bands of θ (H = 249.993, P = 0.000), α (H = 251.311, P = 0.000), β (H = 288.834, P = 0.000), γ1 (H = 312.145, P = 0.000), γ2 (H = 263.777, P = 0.000), γ3 (H = 238.691, P = 0.000), γ4 (H = 208.830, P = 0.000), the differences in the electrocorticographic signal activity characteristics among the 3 groups were statistically significant. Further pairwise comparisons revealed that the electrocorticographic signal activity characteristics of the normal brain tissue group were higher than those of the tumor-invaded cortex group in the frequency bands of θ (Z = 5.711, P = 0.000), α (Z = 5.823, P = 0.000), β (Z = 6.907, P = 0.000), γ1 (Z = 7.286, P = 0.000), γ2 (Z = 6.054, P = 0.000), γ3 (Z = 5.247, P = 0.000), γ4 (Z = 4.647, P = 0.000), and higher than those of the tumor-non-invaded cortex group in the frequency bands of θ (Z = 4.051, P = 0.000), α (Z = 3.277, P = 0.001), β (Z = 4.172, P = 0.000), γ1 (Z = 5.013, P = 0.000), γ2 (Z = 4.749, P = 0.000), γ3 (Z = 4.264, P = 0.000). The electrocorticographic signal activity characteristics of the tumor-non-invaded cortex group were higher than those of the tumor-invaded cortex group in the frequency bands of θ (Z = - 2.071, P = 0.038), α (Z = - 2.871, P = 0.004), β (Z = - 2.403, P = 0.016). Conclusions This study found that normal brain tissue exhibits higher activity characteristics in electrocorticographic signals compared to glioma tissue. These findings suggest the potential for developing glioma localization techniques based on electrocorticographic signals, which could assist neurosurgeons in achieving more precise glioma resection.